VMware Horizon View essentials : successfully design, install, and configure an end-to-end VDI infrastructure with VMware Horizon View - Oven, Peter von (Professional expertise distilled., 2014)
If you are a desktop administrator or an end user of a computing project team looking to speed up to the latest VMware Horizon View solution, then this book is perfect for you. It is your ideal companion to deploy a solution to centrally manage and virtualize your desktop estate using Horizon View 6.0.